Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Guru - Satria Ananda Putra; Uswatun Hasanah; Eko Suparyanto (Amal Insani Foundation, 2023)
This study aims to examine how leadership and organizational culture affect teacher performance. This study uses quantitative research methods with a causality approach. The population in this study was 32 teachers, while the sample used was 32, where the sampling technique used saturated samples, which means that the entire population was sampled. The results of this study are that leadership has a positive and significant effect on teacher performance. Then organizational culture has a positive and significant effect on teacher performance. Furthermore, simultaneously leadership and organizational culture on teacher performance have a positive and significant influence.